PANDANGAN IBNU JARIR AT-THABARI TENTANG KEDUDUKAN WANITA SEBAGAI HAKIM DAN IMAM SALAT - Ali Trigiyatno (Universitas Islam Negeri K.H. Abdurrahman Wahid Pekalongan, 2014)
Study about the defense of women's rights was not only done by scholars today. Classical scholars who died in 310 H named Ibn Jarir At-Thabari has shown concern as well as defense of women's rights, even though he should at odds with the opinion of the majority of scholars at that time. Recorded two controversial fatwa in his time the priesthood of women's issues in front of the man and his status as court judges. His opinion that assessed syadz in his time was now beginning to be used and practiced in many Muslim countries